2016
DOI: 10.1093/hmg/ddw258
|View full text |Cite
|
Sign up to set email alerts
|

Selective mitochondrial depletion, apoptosis resistance, and increased mitophagy in human Charcot-Marie-Tooth 2A motor neurons

Abstract: Charcot-Marie-Tooth 2A (CMT2A) is an inherited peripheral neuropathy caused by mutations in MFN2, which encodes a mitochondrial membrane protein involved in mitochondrial network homeostasis. Because MFN2 is expressed ubiquitously, the reason for selective motor neuron (MN) involvement in CMT2A is unclear. To address this question, we generated MNs from induced pluripotent stem cells (iPSCs) obtained from the patients with CMT2A as an in vitro disease model. CMT2A iPSC-derived MNs (CMT2A-MNs) exhibited a globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 82 publications
4
62
2
Order By: Relevance
“…Human fibroblast cell lines were obtained from Eurobiobank with informed consent (ethical committee approved at the IRCCS Foundation Ca’ Granda Ospedale Maggiore Policlinico). Fibroblasts were generated from dermal biopsies following informed consent as described previously65. Generation of iPSCs was performed by non-viral transduction with six reprogramming factors (OCT4, SOX2, NANOG, LIN28, c-Myc, and KLF4)66.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human fibroblast cell lines were obtained from Eurobiobank with informed consent (ethical committee approved at the IRCCS Foundation Ca’ Granda Ospedale Maggiore Policlinico). Fibroblasts were generated from dermal biopsies following informed consent as described previously65. Generation of iPSCs was performed by non-viral transduction with six reprogramming factors (OCT4, SOX2, NANOG, LIN28, c-Myc, and KLF4)66.…”
Section: Methodsmentioning
confidence: 99%
“…MN differentiation was performed as previously described6566. Briefly, cells were plated with neuronal medium DMEM-F12 (Life Technologies) supplemented with MEM nonessential amino acids solution (Life Technologies), N2 (Life Technologies), and 2 mg/ml heparin (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rizzo F et al . reported that motor neurons derived from iPS cells of CMT2A (MFN2) patients show defects in mitophagy (44), highlighting the importance of mitophagy activity to axonal homeostasis. Identification of the role of mitophagy in peripheral neuropathies is expected to present new therapeutic potentials.…”
Section: Role Of Mitophagy In Human Diseasesmentioning
confidence: 99%
“…MFN2 deletion in HeLa cells has also been shown to affect cell proliferation due to autophagy impairment (Ding et al, 2015). Motor neurons derived from iPSCs obtained from CMT2A patients show increase in mitophagy and mitochondrial depletion and increased expression of PINK1, PARK2 and BNIP3, known triggers for autophagic degradation of mitochondria (Rizzo et al, 2016). In a MFN2 KO mouse model, sarcopenia is seen in correlation with impaired autophagy in the muscle, accumulation of damaged mitochondria, and activation of an adaptive mitophagy pathway (Sebastián et al, 2016).…”
Section: Gene Function Classificationmentioning
confidence: 99%